(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
Unfortunately, diabetes today is still one of the most important medical and social problems worldwide. This disease is often accompanied by hyperglycemia, that is, high blood glucose levels, which in turn leads to damage to many body systems. Of course, at the moment there are methods of effective control and treatment of the disease. Against this background, over the past decade, there has been a marked increase in interest in the methods of complementary and alternative medicine. Some researchers report that up to 72.8% of people with diabetes have used herbal medicine, dietary supplements, and other complementary-alternative medicine methods, in most cases as an adjunct to conventional medical treatment. Many herbal remedies have antioxidant properties that can reduce the level of oxidative stress, one of the key pathogenetic factors in the development of diabetes